PENERAPAN PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN HASIL BELAJAR MATERI SPLDV PADA SISWA KELAS VIII - Oktavianus Rikardus; Sofia Sa'o; Maria Trisna Sero Wondo (Program Studi Pendidikan Matematika, 2021)
This study aims to determine: (1) student activities and teacher activities after the application of Inquiry learning on the material for SPLDV class VIII SMP Negeri 3 Ndona; (2) Can Inquiry learning to improve student learning outcomes in the VIII grade SPLDV material at SMP Negeri 3 Ndona. The type of research used is classroom action research. This research was conducted at SMP Negeri 3 Ndona. The research subjects were 23 people. The instruments used were observation sheets and tests. Data analysis used data analysis learning outcomes and observation data analysis. The showed that the application of Inquiry learning in mathematics learning can improve student learning outcomes for class VIII SMP cycle I to cycle II is 34.8%. The results analysis of observations on student activities in the first cycle showed a percentage of 66.4% and in the second cycle, the percentage was 89.2%. So student activity increased from cycle I to cycle II by 22,8%. While observations of teacher activity in the first cycle showed a percentage of 71.4% and in the second cycle, the percentage of teacher activity was 90% d. So teacher activity increased from cycle I to cycle II with an increase of 18.6%.